Penerapan Teknologi Multiplayer pada Sistem Pembelajaran Berbasis Virtual Reality: Studi Kasus pada Kelas Narotama - Abimanyu, Aditya; Rizqi, Maulana (Jurnal Ilmu Komputer dan Bisnis, 2024)
Virtual Reality is a technology that makes users seem to be interacting with their environment even though it is only a computer simulation. This research explores the application of multiplayer virtual reality (VR) technology in a learning system for assembling LAN cables. By combining elements of learning videos and accessible virtual environments together, this research aims to create a collaborative and immersive learning experience. By utilizing multiplayer technology, users can interact in real-time with fellow students, creating a collaborative and engaging learning experience. by paying attention to aspects of conceptual understanding, technical skills, and collaboration between students in a multiplayer virtual environment. This research also focuses on aspects of implementing virtual reality technology to create deeper and more immersive learning simulations. The main goal of this research is to increase interactivity and engagement of students in virtual learning environments.